Transabdominal and transvaginal ultrasound findings help to guide the clinical management of placenta accreta spectrum cases - Rozi Aditya Aryananda; Johannes J. Duvekot; Heleen J. Van Beekhuizen; Nareswari Imanadha Cininta; Grace Ariani; Erry Gumilar Dachlan (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The clinical management of placenta accreta spectrum (PAS) depends on placental topography and vascular involvement. Our aim was to determine whether transabdominal and transvaginal ultrasound signs can predict PAS management. Material and methods We conducted a retrospective cohort study of consecutive prenatally suspected PAS cases in a single tertiary‐care PAS center between January 2021 and July 2022. When PAS was confirmed during surgery, abdominal and transvaginal ultrasound scans were analyzed in relation to PAS management. The preferred surgical approach of PAS was one‐step conservative surgery (OSCS). Massive blood loss and PAS topography in the lower bladder trigone necessitated cesarean hysterectomy. Transvaginal ultrasound‐diagnosed intracervical hypervascularity was split into three categories based on their quantity. Anatomically, the internal cervical os is located at the level of the bladder trigone and was used as landmark for upper and lower bladder trigone PAS. Results Ninety‐one women underwent OSCS and 35 women underwent cesarean hysterectomy (total 126 women with PAS). Abdominal and transvaginal ultrasound features differed significantly between women that underwent OSCS and cesarean hysterectomy: decreased myometrial thickness (<1 mm), 82.4% vs. 100%, p = 0.006; placental bulge, 51.6% vs. 94.3%, p < 0.001; bladder wall interruption, 62.6% vs. 97.1%, p < 0.001; abnormal placental lacunae, 75.8% vs. 100%, p < 0.001; hypervascularity (large lacunae feeding vessels, 57.8% vs. 94.6%, p < 0.001; parametrial hypervascularity, 15.4% vs. 60%, p < 0.001; the rail sign, 6.6% vs. 28.6%, p = 0.003; three‐dimensional Doppler intra‐placental hypervascularity, 81.3% vs. 100%, p < 0.001; intracervical hypervascularity 60.4% vs. 94.3%, p < 0.001); and cervical length 2.5 ± 0.94 vs. 2.2 ± 0.73, p = 0.038. Other ultrasound signs were not significantly different. The results of multivariable logistic regression showed placental bulge (odds ratio [OR] 9.3; 95% CI 1.9–44.3; p = 0.005), parametrial hypervascularity (OR 4.1; 95% CI 1.541–11.085; p = 0.005), and intracervical hypervascularity (OR 9.2; 95% CI 1.905–44.056; p = 0.006) were weak predictors of OSCS. Intracervical hypervascularity Grade 1 (vascularity <50% of cervical tissue) was more present in OSCS than higher gradings two and three (91% vs. 27.6% vs. 14.3%; p < 0.001). Conclusions Cesarean hysterectomy is associated with the PAS signs of placental bulge and Grade 2 and 3 intracervical hypervascularity. OSCS is associated with intracervical hypervascularity Grade 1 on transvaginal ultrasound. Prospective validation is required to formulate predictors for PAS management.